More-than-human cities: Where the wild things are. Issue 106 (November 2019) - Steele, Wendy; Wiesel, Ilan; Maller, Cecily
Abstract: In this paper we engage the twin concepts of 'the stray' and 'the friend' for developing empathetic imaginings towards ethical practices in the city. We build on Gruen's (2015) notion of 'entangled empathy' as a critical pathway for realising more-than-human cities. Critical theory, frameworks and methods work to challenge anthropocentrism, shifting the boundaries used to define the Anthropos, and decentring homo urbanis as the defining reference point for ethical action. Drawing on assemblage-methods around diagramming and sketching we outline a more-than-human urban politics. In the urban archipelagos of the Anthropocene, 'where the wild things are' is a shared habitat called the city. As conceptual signifiers, we argue both stray and friend offer examples of new relational possibilities of a more-than human politics for cities that currently exist, and for those yet to come.